Downton Abbey : the grand finale [videorecording (Blu-Ray)] - Fellowes, Julian; Beale, Simon Russell; Bonneville, Hugh; Carmichael, Laura, 1986-; Carter, Jim, 1948-; Cassidy, Raquel, 1968-; Coyle, Brendan; Dockery, Michelle, 1981-; Doyle, Kevin, 1961-; Fox, Michael, 1989-; Froggatt, Joanne, 1980-; Froushan, Arty; et al. (Universal Studios, 2025)
The cinematic return of the global phenomenon follows the Crawley family and their staff as they enter the 1930s. When Mary finds herself at the center of a public scandal and the family faces financial trouble, the entire household grapples with the threat of social disgrace. The Crawleys must embrace change as the staff prepares for a new chapter with the next generation leading Downton Abbey into the future.